Thank you for registering.

One of our academic counsellors will contact you within 1 working day.

Please check your email for login details.
MY CART (5)

Use Coupon: CART20 and get 20% off on all online Study Material

ITEM
DETAILS
MRP
DISCOUNT
FINAL PRICE
Total Price: Rs.

There are no items in this cart.
Continue Shopping

Show that SinA/(secA+tanA-1) + cosA/(cosecA+cotA-1) = 1

Show that SinA/(secA+tanA-1) + cosA/(cosecA+cotA-1) = 1

Grade:10

1 Answers

Arun
25763 Points
4 years ago
sinA/(1/cosA+sinA/cosA-1)+cosA/(1/sinA+cosA/sinA-1)
=sinA/{(1+sinA-cosA)/cosA}+cosA/{(1+cosA-sinA)/sinA}
=sinAcosA/(1+sinA-cosA)+sinAcosA/(1+cosA-sinA)
=sinAcosA[(1+cosA-sinA+1+sinA-cosA)/(1+sinA-cosA)(1+cosA-sinA)]
=2sinAcosA/(1+sinA-cosA+cosA+sinAcosA-cos²A-sinA-sin²A+sinAcosA)
=2sinAcosA/{1+2sinAcosA-(sin²A+cos²A)}
=2sinAcosA/(1+2sinAcosA-1)
=2sinAcosA/2sinAcosA
=1 (Proved)

Think You Can Provide A Better Answer ?

Provide a better Answer & Earn Cool Goodies See our forum point policy

ASK QUESTION

Get your questions answered by the expert for free